Diffusional interaction and phase formation in nickel–aluminum films - S.N. Akhkubekova; V.K. Kumykov; M.Z. Laipanov; A.R. Manukyants; V.A. Sozaev; B.M. Khubolov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2017)
In the present paper bimetal nickel –aluminum films are obtained in vacuum by method of the contact melting at temperature 650°C. The eutectic formations which appear on the surfaces of the films due to diffusion are detected by method of the raster-type electron microscopy.